Neural inductive biases for sequential recommendation - He, Chaoyue (Nanyang Technological University, 2025)
In today's data-driven world, recommendation systems are indispensable for personalizing content to user preferences. Within this field, sequential recommendation—focused on ordered or timestamped user interactions—plays an essential role in anticipating future actions.